Строительство тепловых и атомных электростанций: справочник строителя: в 2-х томах - Турчин Н. Я. Николай Яковлевич; Агеев Г. С. Георгий Сергеевич; Алексеев И. А. Иван Алексеевич; Богачев Е. В. Евгений Владимирович; Винницкий Д. Я. Давид Яковлевич; Непорожний П. С. Петр Степанович (Справочник строителя)
Авт. указаны на обороте тит. л.